Targeting and Insertion of Membrane Proteins in Mitochondria - Eaglesfield, Ross; Tokatlidis, Kostas (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial membrane proteins play an essential role in all major mitochondrial functions. The respiratory complexes of the inner membrane are key for the generation of energy. The carrier proteins for the influx/efflux of essential metabolites to/from the matrix. Many other inner membrane proteins play critical roles in the import and processing of nuclear encoded proteins (~99% of all mitochondrial proteins). The outer membrane provides another lipidic barrier to nuclear-encoded protein translocation and is home to many proteins involved in the import process, maintenance of ionic balance, as well as the assembly of outer membrane components. While many aspects of the import and assembly pathways of mitochondrial membrane proteins have been elucidated, many open questions remain, especially surrounding the assembly of the respiratory complexes where certain highly hydrophobic subunits are encoded by the mitochondrial DNA and synthesised and inserted into the membrane from the matrix side. This review will examine the various assembly pathways for inner and outer mitochondrial membrane proteins while discussing the most recent structural and biochemical data examining the biogenesis process.